Building collaborations that count - Jain, Harsha; Gartaula, Hom; Puskur, Ranjitha; Shivhare, Richa (Rice Today, 2024)
The CGIAR Gender Equality Initiative aims to bundle socio-technical innovations with women at the center to empower and build their resilience against climate-change challenges. The Theory of Change framework highlights the pathways and the most relevant stakeholders to engage to reach shared goals.